The synergy effect of carbon/glass/epoxy hybrid laminate in Mode I delamination: A physical microfracture analysis - Maciel Monticeli, Francisco [UNESP] (2020)
The adoption of carbon/glass fiber hybrid composites is an economical alternative to high-cost carbon/epoxy composites and helps to address environmental issues. However, the addition of another type of fiber modifies the mechanical behavior of the composite regarding interfacial interactions, consequently affecting other properties. Research related to three interfaces, with regard to hybrid composites, has not yet provided a good understanding of the physical interactions between components at a hybrid interface and how they affect the interfacial adhesion. In order to partially understand the interactions occurring in the proposed material, the fracture toughness in Mode I delamination was analyzed based on microstructural fracture mechanisms (FBZ) and energy balance principle models. The addition of flexible glass fiber in a stiffer carbon fiber lay-up enabled a considerable increase in the delamination strength. This property is also attributed to the organosilane adhesion promoter, a natural silane present in glass fiber. Additionally, the increased strain energy release is physically influenced by the rougher fracture surface and the hybrid fiber bridging failure mechanisms, inducing a more stable crack propagation and higher fracture toughness, compared to a carbon fiber composite.